Reliable Path Selection Packet Forwarding Routing Protocol for Vehicular Adhoc Networks - Irshad Ahmed, Abbasi (Universiti Malaysia Sarawak (UNIMAS), 2019)
Vehicular Adhoc Networks (VANETs) have earned a gigantic consideration in the recent era. Wide deployment of VANETs for enhancing traffic safety, traffic management, and assisting drivers through elegant transportation system is facing several research challenges that need to be addressed. One of the crucial issues comprise of the design of scalable routing algorithms that are robust to rapid topology changes and frequent link disconnections caused by high mobility of vehicles. The objective of this research is to develop an optimal and reliable multi-hop routing approach for accomplishing effective vehicular communication in VANETs. First of all, a detailed technical analysis, comparison, and drawbacks of the existing state of the art routing protocols are given. Then, a novel routing scheme called a Reliable Path Selection Packet Forwarding Routing Protocol (RPSPF) is proposed. The novelty of the proposed protocol comes from the fact that firstly it establishes an optimal route for vehicles to send packets towards their respective destinations by considering connectivity and shortest optimal distance based on multiple intersections. Secondly, it uses a novel reliable packet forwarding technique in-between intersections that avoids packet loss while forwarding packet due to occurrence of sudden link ruptures. The performance of the protocol is assessed through GloMoSim and VanetMobiSim simulators. According to the simulation analysis, RPSPF protocol exhibits higher packet delivery ratio by 40%, 30%, 25% and 18%. It also experiences much lower end to end delay by 50%, 40%, 25% and 20% as compared to the state of the art routing protocols like Greedy Perimeter Stateless Routing (GPSR), Directional Greedy Source Routing (DGSR), Enhanced Greedy Traffic Aware Routing Directional (E-GyTARD), and Traffic Flow Oriented Routing (TFOR) respectively. It also experiences very lower routing overhead as compared to aforementioned protocols. The proposed routing protocol has significantly enhanced network performance by incorporating the routing challenges in effective manners. The scheme is envisaged to function well for various kinds of vehicular communication applications by assuring user connectivity. These applications consist of road safety services such as coordinated communication of two vehicles, managing flows of traffic, triggering driving related alerts such as traffic congestion alerts, road situation alerts, and accident warnings. Other applications include finding locations of petrol stations and restaurants, accessing internet, downloading music, and playing games.